The Strategic Community-Based Firm - Kodama, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2007)
This book considers the concept of strategic community, a framework that integrates knowledge possessed by people, groups or organizations across boundaries. Case studies demonstrate how strategy, organization and leadership in corporations, represent the dynamic view of strategy necessary to obtain competitive organizational capability.
Keywords: Leadership; Business Strategy/Leadership.